UPAYA GURU DALAM MELAKSANAKAN PEMBELAJARAN DARING PADA MASA PANDEMI COVID-19 - Muhammad Mastur; Mohammad Afifulloh; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
The implementation of physical distancing policy during the Covid-19 pandemic which later became the basis of the world of education to carry out learning activities from home by utilizing information technology suddenly, made teachers and students feel surprised including the parents of students. The purpose of this study is to describe the efforts of MI Miftahul Huda teachers in implementing online learning during the Covid-19 Pandemic period, to describe the applications used by MI Miftahul Huda teachers in implementing Online learning during the Covid-19 Pandemic period, and to describe the factors that support and inhibit in implementing online learning during the Covid-19 Pandemic. This research was conducted with a qualitative method using data collection techniques consisting of observation, interviews, and documentation. The results of this researc are the efforts made by MI Miftahul Huda's teacher in implementing online learning during the Pandemic Covid-19 period using information technology and social media at home. The applications and media used by teachers are Whats App, Google Form, Learning Broadcast on TVRI, Zoom Cloud Meeting, and Dragon Learn. Factors that support the implementation of online learning are the availability of Android Mobile devices for most guardians of students and there is ease of communication between teachers and parents about student learning activities at home by using the WhatsApp group. While the inhibiting factors include undisciplined in terms of time and the role of education tends to be more to parents and teachers only as facilitators. Keyword: Teacher efforts, online learning